Time-dependent effects of systemic lipopolysaccharide injection on regulators of antioxidant defense Nrf2 and PGC-1alpha in neonatal rat brain. - Correa, Fernando Gabriel (2013)
Background/Aims: Both excitotoxicity and neuroinflammation are associated with oxidative stress. One transcription factor, nuclear factor E2-related factor 2 (Nrf2), and one transcription cofactor, peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α), increase the endogenous antioxidant defence and can thus modulate neuronal cell death. Here, we investigated the temporal effects (after 24 and 72 h) of systemic (i.p.) administration of lipopolysaccharide (LPS) on the cerebral Nrf2 and PGC-1α systems. Methods and Results: Seven-day-old rat pups were injected with LPS (0.3 mg/kg). After 24 h, the protein levels of γ-glutamylcysteine ligase modulatory subunit, γ-glutamylcysteine ligase catalytic subunit, Nrf2, PGC-1α and manganese superoxide dismutase (MnSOD) were increased in parallel with decreased levels of Keap1. These effects were correlated with an increased level of phosphorylated Akt and elevated acetylation of histone 4. In contrast, 72 h following LPS, a decrease in the components of the Nrf2 system in parallel with an increase in Keap1 was observed. The down-regulation after 72 h correlated with phosphorylation of p38 mitogen-activated protein kinase, while there were no changes in PGC-1α and MnSOD protein levels or the acetylation/methylation pattern of histones. Conclusion: Systemic LPS in neonatal rats induced time-dependent changes in brain Nrf2 and PGC-1α that correlated well with the protective effect observed after 24 h (pre-conditioning) and the deleterious effects observed after 72 h (sensitizing) of systemic LPS reported earlier. Collectively, the results point towards Nrf2 and PGC-1α as a possible mechanism behind these effects.